Success in conceptual age : the creative human resources needed - Ab. Aziz Shuaib; Olalere, Folasayo Enoch
With the global trend tending towards the conceptual age, the economy and society built on the logical order of the information age is now tending towards emotional and perceptual world. Therefore, consumers now demands to be treated individually because they no longer want product that just do the right thing but also make them feel the right way. With this trend, it’s now necessary for the creative workers to change their mind-set and build their innovative and creative skills towards the upcoming conceptual age. In the light of this, this paper gives the general overview of the developmental and design trend, illuminates on the characteristics of creative workers required in the conceptual age and also proposed the types of trainings needed to build their innovative and creative skills for the coming conceptual age.